Microbeads and microcapsules for diet delivery to Zelus renardii - Ugo Picciotti; Giuseppe Francesco Racaniello; Marianna Ivone; Pasquale Trotti; Angela Assunta Lopedota; Paolo Damiani; Francesca Garganese; Nunzio Denora; Francesco Porcelli (PLoS ONE, 2025)
Predation on Aphrophoridae and other olive tree pests makes Zelus renardii a candidate for biocontrol actions to limit Xylella fastidiosa infections while mitigating other olive tree pests. The opportunity drives the search for an effective mass rearing method of Z. renardii. Predator rearing on artificial diets greatly benefits from feed-effective formulation, preparation, storage, preservation, and delivery. Given the several oligidic, meridic, and holidic available formulations, we face the challenge of a proper diet processing for delivery. To understand how to obtain a large number of preservable and sterile diet portions while avoiding microbial contamination, we explore prilling/vibration techniques to rear Z. renardii. Prilling or vibrating the diets yields multicore microbeads or monocore microcapsules; water domains exist, whose arrangements are well-documented by the cryo-SEM study and represented in corresponding false-color images. Issues include the density interplay between low- or high-density alginate and the liquid diet formulation during prilling/vibration. Other options relate to alginate stickiness or consistency, which makes it difficult to disperse the diet domains in the microbeads or to obtain a single diet domain per microcapsule because of unpredictable wall thickness and core lateralization. We suggest options to make microbeads and microcapsule portions available for up to one year for predators, stored in cold, pure water.